The Impact of Cultural Tourism Industry Policy on Guizhou Travelers' Usage Satisfaction - Chuachun Tang; Jacky Mong Kwan Watt (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores the impact of cultural tourism industry policy on travelers' usage satisfaction. As a cornerstone of the industry that advances the cultural sector, tourism plays a crucial role in promoting the realization of high-quality culture and tourism goals and significantly contributes to overall economic development. The potential insights on tourist satisfaction, essential for upgrading scenic spots, attracting tourists, improving service quality and user satisfaction, building an independent tourism brand, driving employment, and promoting regional economic development, are revealed in this study involving 380 respondents. The results show that tourists’ usage satisfaction with cultural tourism industry policy is influenced by policy perception, policy implementation, and overall policy development.